Brief report: International perspectives on the pediatric COVID‐19 experience. Issue 7 (1st May 2020) - Yilmaz, Ozge; Gochicoa‐Rangel, Laura; Blau, Hannah; Epaud, Ralph; Lands, Larry C.; Lombardi, Enrico; Moore, Paul E.; Stein, Renato T.; Wong, Gary W. K.; Zar, Heather J.
Abstract: The 2019 novel coronavirus (SARS‐CoV‐2) is endangering human health worldwide; scarcity of published pediatric cases and current literature and the absence of evidence‐based guidelines necessitate international sharing of experience and personal communication. On 31 March 2020 the International Committee of the American Thoracic Society Pediatrics Assembly recorded an online podcast, during which pediatric pulmonologists worldwide shared their experience on the novel coronavirus disease (COVID‐19) in children. The aim was to share personal experience in organizing pediatric care in different health care settings globally, protecting health care workers, and isolation practices. This manuscript summarizes the common themes of the podcast which centered around three main topics: more benign clinical disease and progression in pediatric cases compared to adults, a strong need for strategies to protect health care workers, and social or economic disparities as a barrier to successful pandemic control.